The Effect of Application of Caring Theory Model on Satisfaction of Hospitalized Patient - Sutarmi; Yannerith Chintya (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
Humanistic care plays an important role in improving the quality of health services, particularly through the application of the Caring Theory Model, which emphasizes empathic relationships between healthcare providers and patients. This approach is expected to enhance patient satisfaction during hospitalization. Purpose: This study aimed to analyze the effect of the application of the Caring Theory Model on patient satisfaction levels in the inpatient unit of RSUD dr. Rasidin Padang. Methods: The study used a quasi-experimental design involving 25 inpatients. Data were collected using structured questionnaires to assess patient satisfaction before and after the implementation of the Caring Theory Model. The study was conducted at RSUD dr. Rasidin Padang, in June 2025. Univariate analysis was used to describe the frequency distribution of patient satisfaction levels, while bivariate analysis using paired t-tests was conducted to examine differences in satisfaction before and after the intervention, with a significance level of 0.05. Results: Univariate findings showed that 72% of patients experienced increased satisfaction following the application of the Caring Theory Model, particularly related to emotional care and communication by healthcare personnel, while 28% reported no significant change. Bivariate analysis revealed a statistically significant difference in patient satisfaction before and after the intervention (p = 0.002). Conclusion: The application of the Caring Theory Model has a significant positive effect on patient satisfaction and should be integrated into routine inpatient care to improve service quality.